Funny Stories - Oduwole, Samson Adebayo (Evans Brothers (Nigeria Publishers) Limited, 2008)
This is a spellbinding collection of educative and informative, yet entertaining stories aimed at teaching virtues in a morally deficient society.
Keywords: Collection of Stories; Fiction-Nigeria (English); Traditional Stories